The casein-derived peptide YFYPEL alleviates intestinal epithelial cell dysfunction associated with NEC by regulating the PI3K/AKT signaling pathway. Issue 8 (30th March 2023) - Chen, Wenjuan; Chen, Yanjie; Qian, Yun; Zhang, Jun; Hu, Xiaoshan; Yan, Xiangyun; Jiang, Chengyao; Yao, Shuwen; Yu, Qinlei; Chen, Xiaohui; Han, Shuping
Abstract : The effect of peptides in NEC remains poorly understood. Our study showed that YFYPEL reduced inflammation and enhanced migration by regulating the PI3K/AKT pathway. The peptide may thus develop into a novel modality in NEC treatment. Abstract : Necrotizing enterocolitis (NEC) is a life-threatening risk to the health of neonates, but thus far, there is no very effective treatment. Although many studies have confirmed the therapeutic role of peptides in diseases, the effect of peptides in NEC remains poorly understood. This study investigated the role of casein-derived peptide YFYPEL in NEC cells and animal models. We synthesized YFYPEL and analysed its protective effects on NEC both in vitro and in vivo . YFYPEL integration in the intestine increased rat survival and clinical conditions, lowered the incidence of NEC, alleviated bowel inflammation, and enhanced intestinal cell migration. Furthermore, YFYPEL significantly decreased interleukin 6 expression and increased intestinal epithelial cell migration. Moreover, YFYPEL alleviated intestinal epithelial cell dysfunction through the PI3K/AKT pathway, as demonstrated by western blotting and bioinformatics analysis. A selective PI3K activator reversed the protective effect of YFYPEL on lipopolysaccharide-stimulated intestinal epithelial cells. Our study showed that YFYPEL reduced inflammatory cytokine expression and enhanced migration by regulating the PI3K/AKT pathway. The use of YFYPEL may thus develop into a novel modality in NEC treatment.